2022
DOI: 10.1007/s40519-022-01440-4
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa, mindful eating, and perfectionism: an exploratory investigation

Abstract: Purpose Research has drawn associations between Mindful Eating (ME) and perfectionism in the aetiology and treatment of eating disorders (ED), but understanding into the relationship between these factors and Orthorexia nervosa (ON) is limited. The purpose of this research is to explore the relationship between perfectionism, ME, and ON. Method Participants (n = 670) completed the Düsseldorf Orthorexia scale, the Mindful Eating Behavior scale, and the Big-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Convergent and discriminant validity did significantly replicate previous findings. The scales used for convergent and discriminant validity matched similar non-clinical research with English-speaking samples, and rationales on potential associations to mindful eating can be found in the literature, such as mindful eating and: motivations to eat palatable foods (e.g., [ 33 , 40 ]), orthorexia (e.g., [ 32 , 35 , 52 , 53 ]), emotional eating (e.g., [ 30 , 31 , 52 , 54 ]), cravings (e.g., [ 29 ]), and grazing (e.g., [ 34 ]). Meanwhile, Epicurean eating, preference to supersize and stress-induced eating appear relevant to mindful eating and implications can be drawn from other literature on mindfulness and different levels of sensory attentiveness (e.g., [ 28 , 55 57 ]).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Convergent and discriminant validity did significantly replicate previous findings. The scales used for convergent and discriminant validity matched similar non-clinical research with English-speaking samples, and rationales on potential associations to mindful eating can be found in the literature, such as mindful eating and: motivations to eat palatable foods (e.g., [ 33 , 40 ]), orthorexia (e.g., [ 32 , 35 , 52 , 53 ]), emotional eating (e.g., [ 30 , 31 , 52 , 54 ]), cravings (e.g., [ 29 ]), and grazing (e.g., [ 34 ]). Meanwhile, Epicurean eating, preference to supersize and stress-induced eating appear relevant to mindful eating and implications can be drawn from other literature on mindfulness and different levels of sensory attentiveness (e.g., [ 28 , 55 57 ]).…”
Section: Discussionmentioning
confidence: 96%
“…The availability of other eating behaviour questionnaires validated in the Greek language was limited, forcing a similar forward–backwards translation, as well as an assessment of face validity and internal consistency of a palatable eating motives scale [ 22 ], a grazing scale [ 23 ], a craving scale [ 24 ], an orthorexia scale [ 25 ], an emotional eating scale [ 26 ], a stress eating scale [ 27 ], and an Epicurean eating scale (inclusive of a preference for supersizing sub-scale; see [ 28 ]). Based on corresponding research employing English-speaking samples, we expected motivations to eat palatable foods, emotional eating, cravings, grazing, preference to supersize, stress-induced eating and orthorexia to relate negatively to mindful eating measures (e.g., [ 29 35 ]). Meanwhile, when the preference for supersizing is seen as the opposite polar of Epicurean eating (see [ 28 ]), and Epicurean eating has a description of preference for quality and appreciation of the sensation of food and eating, we expected a positive relationship to mindful eating.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to perfect rules in life is a predictor of mental illness and eating disorders [29]. Higher perfectionism was associated with more orthorexia nervosa in two studies [30][31][32]. Recent findings showed that all dimensions of perfectionism were positively associated with following strict eating rules, and namely, ON [33].…”
Section: Perfectionism Eating Attitudes Orthorexia Nervosa and Mddmentioning
confidence: 99%
“…Dado que es probable que estas personas sean particularmente susceptibles a los problemas relacionados con la salud y la nutrición (3) , en congruencia con un esquema alimentario consciente (44) , pueden sentir la presión de ser modelos a seguir para la salud (45) , y mostrar tendencias hacia el perfeccionismo; vale decir, la persecución de elevados estándares de desempeño, muy críticamente evaluados, con una excesiva preocupación por cometer errores (46) ; el cual puede manifestarse adaptativamente, al suponer la búsqueda funcional y positiva de la excelencia, que posee poca relevancia clínica (47) y que podría detectarse en la ortorexia saludable, cuya esencia configura más bien un estilo de vida, más que un trastorno. En cambio, el tipo de perfeccionismo inherente a la ortorexia nerviosa, representa el aspecto desadaptativo o negativo de éste (48) , ya que concibe la percepción de que permanentemente no se logran cumplir los altos estándares auto-impuestos.…”
Section: Síndrome Ortoréxico Y Perfeccionismounclassified